The invasive alga Gracilaria vermiculophylla in the native northwest Pacific under ocean warming: Southern genetic consequence and northern range expansion - Liu, Yi-Jia; Zhong, Kai-Le; Jueterbock, Alexander; Satoshi, Shimada; Choi, Han-Gil; Weinberger, Florian; Assis, Jorge; Hu, Zi-Min (Frontiers in Marine Science, 2022)
Ocean warming is one of the most important factors in shaping the spatial distribution and genetic biodiversity of marine organisms worldwide. The northwest Pacific has been broadly illustrated as an essential seaweed diversity hotspot. However, few studies have yet investigated in this region on whether and how past and ongoing climate warming impacted the distribution and genetic pools of coastal seaweeds. Here, we chose the invasive species Gracilaria vermiculophylla as a model, and identified multiple genetic lineages in the native range through genome-scale microsatellite genotyping. Subsequently, by reconstructing decadal trends of sea surface temperature (SST) change between 1978 and 2018, we found that SST in northern Japan and the East China Sea indeed increased broadly by 0.25-0.4°C/decade. The projections of species distribution models (SDMs) under different future climate change scenarios (RCP 2.6, RCP 4.5, RCP 6.0 and RCP 8.5) indicated that a unique genetic pool of G. vermiculophylla at its current southern range limit (i.e. the South China Sea) is at high risk of disappearance, and that the populations at its current northern range limit (i.e. in Hokkaido region) will undergo poleward expansions, particularly by the year 2100. Such responses, along with this species’ limited dispersal potential, may considerably alter the contemporary distribution and genetic composition of G. vermiculophylla in the northwest Pacific, and ultimately threaten ecological services provided by this habitat-forming species and other associated functional roles.